Studies on Pyrimidines, Part III: Synthesis and Antibacterial Activity of 6-(2’ -Hydroxy-5’-methylphen-1’ -yl)-3-acetyl-4- substitutedphenyl-3,4-dihydropyrimidine-2-thiols. - CHAMPANERI, H.R.; MODI, S.R.; NAIK., H.B. (Asian Journal of Chemistry, 2010)
3-Acetylpyrimidine-2-thiol derivatives have been prepared by reacting pyrimidine-2-thiones with acetyl chloride. All the compounds have been screened for their antibacterial activity.